Exposure to the ROCK inhibitor fasudil promotes gliogenesis of neural stem cells in vitro - Nizamudeen, Zubair Ahmed; Chakrabarti, Lisa; Sottile, Virginie (Elsevier, 2018)
Fasudil is a clinically approved Rho-associated protein kinase (ROCK) inhibitor that has been used widely to treat cerebral consequences of subarachnoid haemorrhage. It is known to have a positive effect on animal models of neurological disorders including Parkinson’s disease and stroke. However, its cellular effect on progenitor populations and differentiation is not clearly understood. While recent studies suggest that fasudil promotes the mobilization of neural stem cells (NSCs) from the subventricular zone in vivo and promotes the differentiation of the C17.2 cerebellar neuroprogenitor line in vitro, it is unclear whether fasudil is involved in the differentiation of primary NSCs.